2017
DOI: 10.1371/journal.pone.0175322
|View full text |Cite
|
Sign up to set email alerts
|

Electrosensory neural responses to natural electro-communication stimuli are distributed along a continuum

Abstract: Neural heterogeneities are seen ubiquitously within the brain and greatly complicate classification efforts. Here we tested whether the responses of an anatomically well-characterized sensory neuron population to natural stimuli could be used for functional classification. To do so, we recorded from pyramidal cells within the electrosensory lateral line lobe (ELL) of the weakly electric fish Apteronotus leptorhynchus in response to natural electro-communication stimuli as these cells can be anatomically classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 80 publications
(113 reference statements)
1
5
0
Order By: Relevance
“…We waited at least one hour after probe insertion before starting recordings to allow brain tissue to settle following probe insertion and to improve recording stability. Accounting for the fact that the first recording site is located 175 μm away from the tip along the probe shaft, as well as the fact that recordings were typically obtained on recording sites ranging between 13 and 97, this gives approximate recording between 355 and 1195 μm from the brain surface along, which are within the range reported from a previous study where location within LS was confirmed by histological post-processing 82 , 83 . Thus, based on probe geometry, anatomy 81 , and our experience recording from ELL pyramidal cells 58 , 65 , 82 , 84 , 85 , it is likely that most of our recordings were from LS.…”
Section: Methodssupporting
confidence: 73%
“…We waited at least one hour after probe insertion before starting recordings to allow brain tissue to settle following probe insertion and to improve recording stability. Accounting for the fact that the first recording site is located 175 μm away from the tip along the probe shaft, as well as the fact that recordings were typically obtained on recording sites ranging between 13 and 97, this gives approximate recording between 355 and 1195 μm from the brain surface along, which are within the range reported from a previous study where location within LS was confirmed by histological post-processing 82 , 83 . Thus, based on probe geometry, anatomy 81 , and our experience recording from ELL pyramidal cells 58 , 65 , 82 , 84 , 85 , it is likely that most of our recordings were from LS.…”
Section: Methodssupporting
confidence: 73%
“…These results rule out a model in which the two main song modes are processed in separate pathways, and instead support a model in which interconnectivity contributes to generating a continuum of song mode preferences. Such a continuum has been observed in the sensory systems of fish (Sproule and Chacron, 2017; Thompson and Scott, 2016) and sensorimotor cortices of rodents ((Minderer et al, 2019); (Raposo et al, 2014); (Saleem et al, 2013)), and thought to support encoding of a larger array of variables than would be possible with categorical representations (in other words, a more efficient representation). In the fly auditory system, neurons with intermediate preference could encode sound intensity, location, and long timescale features, such as the variable sequence of pulses and sines that make up song bouts (Coen et al, 2014) - behavioral studies demonstrate that females are sensitive to song bout features such as the average duration of song bouts over timescales of minutes (Clemens et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…We tested this by predicting responses at each node in the connectome from the responses of the inputs using a simple linear model (Figure 6) and discovered strong predictability, suggesting that the wiring diagram places a strong constraint on functional responses, consistent with recent studies in the fly olfactory system. 50 Response continuums have been observed in fish 51,52 and rodents, [53][54][55] and are thought to support more efficient encoding than would be possible with categorical representations. In the fly auditory system, neurons with intermediate preference (that respond roughly equally to sine and pulse) could encode sound intensity, location, and/or long timescale features, such as the variable sequence of pulses and sines that make up song bouts.…”
Section: Discussionmentioning
confidence: 99%